Gastropleural fistula after esophageal cancer resection – a case report - Dzięgielewski, Piotr; Bernacki, Andrzej; Cybulski, Adam; Gułaj, Cezary; Łapuć, Grzegorz; Laudański, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
A case report of 52 years old patient with diagnosis of lower esophagus squamous cell carcinoma infiltrating lower right lobe of the lung with abscess symptoms. We performed a lower right lobectomy and concomitant esophageal resection of medial and lower part (modo Ivor Lewis). In 11th day after operation the patient developed symptoms of multilocular right sided pleural empyema and was straightly reoperated. We revealed disruption of ventricular stapler suture and performed resuturing ventricular wall and lung decortication. Patient was discharged after 15 days post second procedure and survived for 18 months untill death due to non-malignant etiology.